2013
DOI: 10.1016/j.ijid.2013.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Older HIV-infected patients—an underestimated population in northern Greece: epidemiology, risk of disease progression and death

Abstract: HIV-infected people aged ≥50 years differ in epidemiological and clinical features to younger HIV-infected people. The issue of increasing prevalence of HIV infection is a matter of concern due to existing comorbidities, which probably lead to higher mortality rates and faster progression to clinical AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 50 publications
5
25
2
4
Order By: Relevance
“…Incidence of HIV infection might have been as high among older adults as it was among youths but the picture was unclear because they have been more or less neglected in HIV testing and prevention programmes 6 . Most of the current knowledge about the characteristics of HIV infection in older persons has come from the developed countries in North America 7,8 and Europe [9][10][11] . The pattern has also been described in China 12,13 and Taiwan…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidence of HIV infection might have been as high among older adults as it was among youths but the picture was unclear because they have been more or less neglected in HIV testing and prevention programmes 6 . Most of the current knowledge about the characteristics of HIV infection in older persons has come from the developed countries in North America 7,8 and Europe [9][10][11] . The pattern has also been described in China 12,13 and Taiwan…”
Section: Introductionmentioning
confidence: 99%
“…As expected, this poor health status at presentation predisposes older adults to faster disease progression, poor treatment success and higher mortality. Metallides et al also reported higher prevalence of cardiovascular and neurological conditions among older adults, though these are health conditions associated with old age 9 . Sub-Saharan Africa is lagging behind in terms of literature on the characteristics of HIV infection in older adults.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Among the 19 primary studies reporting data on HIV test uptake, six were performed in the EU/EEA [38][39][40][41][42][43],one in Australia [44] and the remainder in the USA [31,[45][46][47][48][49][50][51][52][53][54][55] (Web Annex Table 6). Generally, the findings pointed at a lower frequency of HIV test uptake among older adults as compared to younger age groups, even if the actual proportion of tested individuals varied greatly between studies.…”
Section: Patterns Of New Hiv Diagnosis and Hiv Test Uptakementioning
confidence: 99%
“…Generally, the findings pointed at a lower frequency of HIV test uptake among older adults as compared to younger age groups, even if the actual proportion of tested individuals varied greatly between studies. Two European [38,40] and several non-EU surveys [44,45,47,51,53,55] reported that 50% to less than 5% older adults, with majority around 25%, had tested for HIV. Three studies reported the level of testing among patients diagnosed with an indicator-condition [39,43,54] to be low generally and significantly lower in older adults than in the younger age groups.…”
Section: Patterns Of New Hiv Diagnosis and Hiv Test Uptakementioning
confidence: 99%